69‐4: Active Backplane Design for Digital Video Walls. Issue 1 (May 2017) - Dykaar, Douglas R.; Tarighat, Roohollah Samadzadeh; Chen, Feng; Davidson-Hall, Tyler; Hill, Graham; Vieth, John; Brown, Chris; Aziz, Hany; Sivoththaman, Siva
Abstract : We report on the design of a scalable active backplane for digitally driven video wall displays. The substrates use single‐crystal silicon spheres which are embedded in ceramic and planarized.